An evaluation of the impact of e-commerce on the quality of financial reports: a case of Soledd finance - Sachikonye, Kudzai (Midlands State University, 2018)
We are living in a dynamic world characterized by spontaneous changes happening in the twinkle of the eye brought about mainly by advances in technology. This research was set out to evaluate the impact of e-commerce on the quality of financial reporting (A case of Soledd Finance). The research was mainly prompted by the observations that the researcher witnessed during industrial attachment experiences within an e-commerce firm. The choice to focus on this study was due to the challenges being faced by the firm in financial reporting which were prompted by a shift from the traditional business to electronic one. The firm is failing to meet reporting deadlines, and experiences longer audit periods, reconciliation difficulties and also material variances in financial statements. A review of literature with information pertaining to changes that have occurred to the financial reporting process under e-commerce was carried out extensively. The findings highlighted that financial reporting in e-commerce is mainly affected by information technology risks and the non-integration of modules. Data was gathered using questionnaires and interviews; both primary and secondary sources were used and analyzed in order to give the researcher a better understanding. The study recommended that Soledd Finance must introduce an accounting system which can easily integrate modules while not altering the activities of the firm and also invest in risk management strategies.